An intelligent travel technology assessment model for destination impacts of tourist adoption - Noppadol Phaosathianphan (2022)
As intelligent travel technology creates a business trend to support the travel and tourism industry, it is necessary to create a complete model to assess the users in terms of continuous user acceptance and destination impacts which are Competitiveness, Loyalty, and Sustainability with entire stakeholders (travellers, service providers, and destinations). The proposed conceptual model is formulated based on four studies: A Plenary Free Individual Traveler Life Cycle, IS Success, IS Continuance, and Destination Impacts of Travel and Tourism. The sample and data collections were done through the online questionnaire and survey via social media platforms such as Facebook and Line with individuals who have used intelligent personal assistants such as Google Assistant, Apple Siri, Microsoft Cortana, Amazon Alexa, and Samsung Bixby for travel and tourism. 400 respondents were analyzed with descriptive statistics and inferential statistics using the measurement model and the structural model by PASW Statistics and SmartPLS.